Analisis Ekspor Jahe Indonesia ke Enam Negara Tujuan Utama Tahun 2010-2020 - L.M. Rizal; Wahyudin Wahyudin (Seminar Nasional Official Statistics, 2022)
Indonesia is one of the world's largest exporters of ginger, however, the export performance of Indonesian ginger in recent years has decreased. This study aims to obtain an overview of the development of Indonesian ginger export volumes to the six main destination countries, examine the export competitiveness of Indonesian ginger against India and Thailand, and analyze the determinants of Indonesian ginger exports to the six main destination countries in 2010-2020. The analytical methods used are RCA, EPD, X-Model Potential Export Products, and panel data regression unbalanced gravity model approach with the best model FEM. The results of this study indicate that the development of Indonesian ginger exports to the six main destination countries has tended to decline in recent years. Furthermore, the competitiveness of Indonesian ginger is superior in the main destination countries of Bangladesh, Malaysia, Singapore, and Vietnam when compared to its competitors, India and Thailand. In addition, the Indonesian RCA variable, the real GDP per capita of the destination country, the economic distance, and the real price of ginger exports have a significant effect on the export volume of Indonesian ginger.